The roles of polyamines in ESKAPE pathogens - Jackson, Samuel G. (2024)
Klebsiella pneumoniae and Acinetobacter baumannii are two of the ESKAPE pathogens that are responsible for a large number of nosocomial infections globally. Increasing levels of multidrug resistance make both organisms of critical concern for developing new therapeutic strategies. A possible approach for this is to target polyamine synthesis. Polyamines are small polycationic molecules that are derived from amino acids, that are found across all domains of life. In bacteria polyamine synthesis pathways are not conserved between species and polyamines do not have a conserved function, as they do in mammalian cells. They have been found to contribute to growth, gene expression, biofilm formation, motility, and stress resistance. Previous investigations have shown a link between polyamines and the virulence factors of K. pneumoniae and A. baumannii. This study has shown that loss of 1, 3-diaminopropane synthesis, in A. baumannii impacts growth and results in a cell septation defect. Chemical complementation indicates a requirement for 1, 3-diaminopropane with other di- and triamines unable to chemically complement a Δddc 1, 3-diaminopropane null mutant. The Δddc strain also exhibited a lack of surface-associated motility, reduced biofilm formation with overproduction being observed when chemically complemented, a decreased susceptibility to aminoglycosides and attenuated virulence possibly linked to increased susceptibility to antimicrobial elements within the haemolymph of larvae. The loss of 1, 3-diaminopropane synthesis in K. pneumoniae had little impact, with only a reduction in biofilm formation being observed. With regard to cadaverine, deletion of the acid-inducible synthesis pathway in K. pneumoniae demonstrates the ability of cadaverine to contribute to growth in an acidic environment. Additionally, it suggests that cadaverine also provides protection against nitrosative stress in K. pneumoniae but not oxidative stress. This study expands on the current understanding of the role of 1, 3-diaminopropane in A. baumannii and highlights some of the roles of 1, 3-diaminopropane and cadaverine in K. pneumoniae, ultimately providing a foundation for future work to continue investigation into the use of polyamine synthesis as a therapeutic target.